Industrialización de la construcción para la vivienda social: Estudio de casos: España – Colombia (2007)
This article is the outcome of a monographic study that takes construction industrialization as the driving force for technological innovation in solving the lack of housing, that is, in fulfilling the need of a different outlook towards dwelling—a standpoint of a product and not of a process— without losing perspective on the issue of habitability